The genus Spryginia (Brassicaceae) in Iran and Afghanistan - Amiri, Mohammad Sadegh; Mehrvarz, Shahriar Saeidi; Moazzeni, Hamid; Joharchi, Mohammad Reza; Memariani, Farshid; German, Dmitry (Phytotaxa, 2018)
The oligotypic Irano-Turanian mustard genus Spryginia (Brassicaceae, Euclidieae) is revised in Iran and Afghanistan. Species composition and distribution within the region are clarified. Unlike previously believed, the genus includes two (not one) species in the studied area. Both S. afghanica and S. winkleri are distributed in Afghanistan while only the latter species occurs in Iran representing the first record of the genus for the country. Updated morphological descriptions, data on type specimens, ecology, phenology, and distribution map of both species within the studied area are provided. Spryginia winkleri is illustrated based on Iranian material. A modified generic key is also presented.
Gesehen am 02.07.2020